EVALUASI MUTU FISIOLOGIS TERHADAP LIMA VARIETAS BENIH KEDELAI (Glycine max [ L.] merr) PADA PENYIMPANAN SUHU RUANG YANG BERBEDA AKIBAT ANOMALI CUACA EL NINO 2023 - Fitria, Eliza; Agustiansyah, Agustiansyah; Timotiwu, Paul Benyamin; Hidayat, Kuswanta Futas; Purnomo, Purnomo (JURNAL AGROTROPIKA, 2025)
Global climate change such as El Nino has serious impacts on the agricultural sector, especially soybean production which is very sensitive to water shortages. The government is responding by developing superior soybean varieties that are drought-resistant, such as Kemuning 1, Demas 1, and other varieties that have qualities equivalent to imported soybeans. A significant issue in soybean cultivation within tropical regions is the reduction in seed quality during storage, which is related to the high fat content present in orthodox seeds. Therefore, maintaining the physiological condition of the seeds until planting season requires controlling seed storage at optimal temperature and humidity levels. The results demonstrate that both cultivar and temperature affect the physiological quality of soybean seeds. The Grobogan and Dega 1 varieties produce better physiological quality compared to Deja 2, Dena 1, and Detap 1. Storing seeds at cold temperatures is more effective in maintaining seed viability and quality stability. Key words: Seed, soybean, seed storage, physiological quality